2013
DOI: 10.1155/2013/962376
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Star PEG Grafting Method for the Generation of Nonfouling and Nonthrombogenic Surfaces

Abstract: Polyethylene glycol (PEG) grafting has a great potential to create nonfouling and nonthrombogenic surfaces, but present techniques lack versatility and stability. The present work aimed to develop a versatile PEG grafting method applicable to most biomaterial surfaces, by taking advantage of novel primary amine-rich plasma-polymerized coatings. Star-shaped PEG covalent binding was studied using static contact angle, X-ray photoelectron spectroscopy (XPS), and quartz crystal microbalance with dissipation monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…54 Our results are consistent with the literature since MNP@PO-PEG, the one coating exhibiting a lower charge than the others in analysis, needed a 48-fold longer incubation time in order to reach similar intracellular iron intake. This result is also in accordance with other studies that define PEG as one of the best non-fouling agents, [55][56][57][58] and that it also helps the nanoparticles to avoid immunological recognition of the mononuclear phagocyte system, reducing its clearance. Indeed, being a highly hydrophilic polymer, PEG forms a hydration layer leading to steric repulsion.…”
Section: Discussionsupporting
confidence: 92%
“…54 Our results are consistent with the literature since MNP@PO-PEG, the one coating exhibiting a lower charge than the others in analysis, needed a 48-fold longer incubation time in order to reach similar intracellular iron intake. This result is also in accordance with other studies that define PEG as one of the best non-fouling agents, [55][56][57][58] and that it also helps the nanoparticles to avoid immunological recognition of the mononuclear phagocyte system, reducing its clearance. Indeed, being a highly hydrophilic polymer, PEG forms a hydration layer leading to steric repulsion.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma polymer films (PPFs) are widely studied owing to their numerous potential applications mainly in the biomedical field . An important class of PPFs is the nitrogen based films which are used in, for example, influencing the differentiation of mesenchymal stem cells, enhancing the endothelialisation and healing around vascular grafts, serving as cardiovascular stent coatings and creating non‐fouling and antibacterial surfaces, where amine groups on the coating provide anchoring sites to polyethylene glycol and polyvinyl sulphonate coated silver nanoparticles, respectively. N‐rich PPFs comprise of different N functional groups such as amines, nitriles and imines.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the physicochemical characterization confirmed the presence of a polymeric coating on all treated samples. For instance, the water contact angles that were measured for PEGylated samples were statistically different than for plain and plasma-activated titanium controls (Figure 1a) and they were in the range of wettability previously found for other PEG coatings [51,52]. The fact that no statistically significant differences were found in the average roughness (R a ) values of titanium and the PEG coated samples indicated that the coatings did not modify the morphology of the samples.…”
Section: Discussionmentioning
confidence: 67%